Individualiziran pristop kot alternativa obstoječim praksam obravnave ljudi s posebnimi potrebami - Sedmak, Mateja (Annales. Series historia et sociologia, 1998)
In the system of social security and national social policy, the people with special needs (SN) are still helpless individuals, who are to be dealt with by appropriate professional services and suitably qualified personnel. The Slovene system of social security, which is functioning according to the principle, excludes participation and inclusion of the beneficiaries, which isimplicitly reflected in the fact that the offered social services do not satisfy their actual needs. The beneficiaries who cannot adapt to the offered "package" of social services, which have been adjusted fot he needs of an average (non-existent) beneficiary who can be no longer looked after by his or her family ...
Keywords: Koper; socialna pomoč; socialno varstvo